What Recovery Means to Postpartum Women in Treatment for Opioid Use Disorder - Caroline Shadowen; Nancy Jallo; Anna Beth Parlier-Ahmad; Lisa Brown; Patricia Kinser; Dace Svikis; Caitlin E. Martin (Mary Ann Liebert, 2022)
Introduction: Opioid overdose has become a leading cause of pregnancy-associated deaths, particularly in the 1st year postpartum, highlighting the need to better understand how to promote recovery for postpartum women. This mixed-methods study aims to investigate how postpartum women receiving medication for opioid use disorder (MOUD) define recovery and factors associated with recovery progression or inhibition. Methods: Women receiving MOUD 2?6 months postpartum were recruited from an outpatient perinatal addiction clinic. Participants completed electronic measures including the Brief Assessment of Recovery Capital (BARC-10, total score range: 6?60) and semistructured individual interviews. Substance Abuse and Mental Health Services Administration (SAMHSA)'s recovery framework served as the conceptual model for interview guide development. Descriptive statistics were generated for survey responses. A qualitative descriptive approach was used to analyze and report the interview data. Results: On average, participants (n?=?8) were 28.6 years old and taking 19.5?mg/day buprenorphine (range 8?24). Fifty percent identified as white and 37.5% as black. All participants identified as currently in recovery, with mean BARC-10 score 52.5 (standard deviation 4.8). Recovery goals included no use of drugs or alcohol (62.5%), being a better partner/spouse (87.5%), and improving finances (87.5%). Interviews generated themes including recovery as transformative, building resilience, and transforming one's health, relationships, and environment through recovery. Conclusions: Participants defined recovery as a dynamic transformative process, including nonabstinence-based goals consistent with SAMHSA domains coupled with reduced substance use. Central to recovery for our postpartum participants was the sense of self reinforced throughout their recovery journey. Women highlighted the key role of MOUD in their recovery process. Findings underscore the need for individualized treatment for postpartum women with opioid use disorder based on their personal goals and will inform development of a validated, gender-informed measure of patient-reported recovery outcomes tailored for this population.